2011
DOI: 10.1245/s10434-011-1906-x
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Impact of Neoadjuvant Chemotherapy on the Tumor Microenvironment of Esophageal Squamous Cell Carcinoma

Abstract: Neoadjuvant chemotherapy utilizing 5-fluorouracil and cisplatin in esophageal squamous cell carcinoma is useful to induce CD4 and CD8 T lymphocytes in the tumor microenvironment and to maintain HLA class I expression levels in combination with its direct cytotoxic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 20 publications
2
42
1
Order By: Relevance
“…18 In esophageal cancer patients, treatment with NAC led to increased numbers of T cells infiltrating tumors. 19 In this study, NAC did not significantly alter the types of immune cells infiltrating primary tumors of bladder cancer patients compared to patients that were chemotherapy naïve (Figure 3). For primary bladder specimens evaluated, 9 patients received NAC and 11 patients were chemo-naïve prior to surgery.…”
Section: Discussionmentioning
confidence: 54%
“…18 In esophageal cancer patients, treatment with NAC led to increased numbers of T cells infiltrating tumors. 19 In this study, NAC did not significantly alter the types of immune cells infiltrating primary tumors of bladder cancer patients compared to patients that were chemotherapy naïve (Figure 3). For primary bladder specimens evaluated, 9 patients received NAC and 11 patients were chemo-naïve prior to surgery.…”
Section: Discussionmentioning
confidence: 54%
“…These new protocols enable the analysis of molecular and pathologic patterns of chemotherapy-treated PDAC. For example, recent preoperative chemotherapy protocols helped to identify the molecular patterns of T cells, showing increased accumulation in tumor tissues in PDAC or oesophageal cancer patients (25,42,43). In addition, in this study we have reported for the first time the distribution of MDSC markers in PDAC patients after chemotherapy treatment, in which MDSCs were the dominant cells in cancer regions.…”
Section: Discussionmentioning
confidence: 63%
“…49 In both mouse models and patients with esophageal squamous cell carcinoma, neoadjuvant chemotherapy with 5-FU and cisplatin increased the intratumoral trafficking of CD4 and CD8 T-cells. 50,51 In experimental carcinogen-induced adenocarcinomas and fibrosarcomas, doxorubicin treatment enhanced tumor-specific proliferation of CD8 T-cells in tumor-draining lymph nodes (LNs) and promoted tumor infiltration of activated, IFN-g-producing CD8 T-cells. 52 In this setting, therapeutic efficacy of doxorubicin required both IL-1b and IL-17, and the presence of gd T-cells.…”
Section: Box 1 Immune-based Effects Of Targeted Anticancer Compoundsmentioning
confidence: 99%